The Effectiveness of Crisis Line Services: A Systematic Review - Hoffberg, Adam S.; Stearns-Yoder, Kelly A.; Brenner, Lisa A. (Frontiers in Public Health, 2020)
Background: Crisis lines are a standard component of a public health approach to suicide prevention. Clinical aims include reducing individuals' crisis states, psychological distress, and risk of suicide. Efforts may also include enhancing access and facilitating connections to behavioral health care. This review examines models of crisis line services for demonstrated effectiveness. Methods: Literature searches of Medline, EMBASE, PsycINFO, Web of Science, CINAHL, Cochrane Library, and Google Scholar were conducted from January 1, 1990, to May 7, 2018. Experts were contacted, and references were mined for additional studies. Eligible studies provided health- or utilization-related effectiveness outcome(s). Results were graded according to the Oxford Centre for Evidence-Based Medicine and evaluated for risk of bias using the Effective Public Health Practice Project quality assessment tool for quantitative studies. Results: Thirty-three studies yielded effectiveness outcomes. In most cases findings regarding crisis calls vs. other modalities were presented. Evaluation approaches included user- and helper-reported data, silent monitoring, and analyses of administrative records. About half of studies reported immediate proximal outcomes (during the crisis service), and the remaining reported distal outcomes (up to four years post-contact). Most studies were rated at Oxford level four evidence and 80% were assessed at high risk of bias. Conclusions: High quality evidence demonstrating crisis line effectiveness is lacking. Moreover, most approaches to demonstrating impact only measured proximal outcomes. Research should focus on innovative strategies to assess proximal and distal outcomes, with a specific focus on behavioral health treatment engagement and future self-directed violence.